Το επαγγελματικό περιβάλλον στα τμήματα ατυχημάτων και επειγόντων περιστατικών(ΤΑΕΠ) των κρατικών νοσηλευτηρίων της Κύπρου - Λάμπρου, Περσεφόνη (Τμήμα Νοσηλευτικής, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
Introduction: Recent research evidence supports that the role of the professional practice environment is crucial for the delivery of quality care as it is significantly correlated with patient and physician/nurse outcomes. The professional practice environment in hospitals is receiving great interest mainly due to the changes that health systems have undergone worldwide but also due to the ongoing global economic crisis. It is obvious that this crisis has a serious impact on employment, given the harsh austerity measures taken by the EU Member States, including cuts in wages, freeze hiring recruitment, suspension of promotions, which have several negative consequences such as loss of expertise, low morale and lack of motivation among professionals and the general decline in living standards of citizens. The health sector, whose budget has undergone drastic reductions, could not be exempted from this vicious cycle. The study of the professional practice environment in Emergency Departments (EDs) is of particular importance because based on current knowledge, it affects the way emergency health care is provided as well as patients’ outcomes and the quality of health services offered to the public. The professional practice environment in public EDs in Cyprus has not been studied extensively and only a few international studies concerning this topic of utmost importance have been carried out. Aim: The purpose of this study was to explore physicians’ and nurses’ perceptions of their professional practice environment in public EDs hospital settings Cypruswide in relation to their job satisfaction and their views on the safety climate and quality of emergency services provided.Method: A descriptive correlational study was performed among all nurses and physicians working in all five public autonomous EDs in July-August 2013 across the island. A total of 277 participants were eligible to participate and 224 questionnaires were completed and returned with an overall response rate of 80,9%. To gain an understanding of the perceptions of the Professional Environment, the Revised Professional Practice Environment-RPPE instrument was used, consisting of 39 questions scaled from 1 to 4 (1 = strongly disagree to 4 = strongly agree), which measures eight characteristics: leadership and autonomy, control over practice, communication about patients, teamwork, handling disagreements, staff relationships, internal work motivation and cultural sensitivity. The two other instruments used were: Warr-Cook-Wall tool (job satisfaction component consisting of 10 items, captured on a 7-point Likert scale) and the Safety Climate Domain of the Emergency Medical Services Safety Attitudes Questionnaire (EMS-SAQ) (consisting of 7 questions scaled from 1-5). One question on a 5-point Likert scale measured the perceptions of the participants as regards quality of the care provided. Furthermore, participants were asked to provide relevant demographic information. The statistical analysis performed included descriptive statistical analysis, correlation tests and univariate and multivariate analysis models. Permissions were granted by the Research Committee of the Cyprus Ministry of Health and the Cyprus National Bioethics Committee. Permissions to use the instruments were obtained directly from the authors. Results: The statistical analyses showed that all the tools used presented satisfactory reliability. Specifically, the Cronbach alpha reliability coefficient was for RPPE 0.88, for job satisfaction 0.90 and for the Safety Climate Domain of the EMS-SAQ 0.62. The mean overall score for RPPE was 2.79 81 (on a scale 1-4), for job satisfaction 4.19 (on a scale 1-7), perceptions of the safety climate 3.18 (on a scale 1-5). and of the quality 3.81 (on a scale 1-5). Physicians assessed higher all indicators. Professionals in the smaller ED gave a higher assessment for all indicators. Statistically significant difference in mean values was recorded between professional groups and certain subscales of the professional environment like "interprofessional relations» (p <0,001), «internal motivation» (p <0,001) and "Cultural sensitivity» (p <0,001). In general, the subscale "teamwork" was assessed with the highest value and "control over practice" with the lowest. Moderate positive correlation was recorded between the Professional Environment and Job Satisfaction (Pearson = 0,67), perceptions about safety climate (Pearson = 0,57) and the quality of care (Pearson = 0,55) with statistically significant difference (p <0,001). "Leadership and autonomy" explained 37% of the variance job satisfaction and 28% of safety climate and the factor "Interprofessional relations" explained 23% of the variance of the quality of care. Discussion: The RPPE index was evaluated in this study with a higher value in comparison to other surveys that included samples from nurses in Cyprus. 'Teamwork' received the highest value that is consistent with research in the US where good teamwork in EDs associated with increased satisfaction with the professional environment. The more positive evaluation of "teamwork" can be attributed to the fact that the ED is a part of the hospital where cooperation with other departments is essential. The factor "Control over practice" received the lowest value which is consistent with the results of other studies that included nurses from Cyprus. Physicians were more satisfied in relation to nurses, and that is evident in other recent studies in Cyprus. The safety climate was not assessed positively which is in line with research in both the Greek and Cypriot area and internationally. The physicians expressed a more positive view on self-reported quality of care that is consistent with international research in the case the sample included both physicians and nurses. Conclusions-suggestions: The results confirm the positive correlation between the professional environment, job satisfaction, and perceptions of safety climate and quality of care. The investigation identified weaknesses in specific characteristics of the Professional Environment, that were assessed with a lower score and these results can be a valuable tool for designing appropriate intervention measures and policies. The findings of this study suggest that investing in a good professional practice environment improves the assessment of the quality of the care provided and the patient safety climate. Our research shows the originality that it simultaneously assesses the perceptions about the Professional Environment of both physicians and nurses. In Cyprus and the wider Greek area, this is the first study which tried to explore these variables at the Accident and Emergency Departments. As regards, its contribution to the international literature it should be noted that the comparison of the perceptions of the two main groups of health professionals - physicians and nurses- in one of the most neuralgic departments of hospitals, and the interconnection of these variables (professional practice environment, job satisfaction, safety climate and quality of care) for which only a few studies exist. Based on the results of the study, interventions could be applied to improve the professional environment which will contribute to increasing the safety climate and quality of care as well as the overall improvement of health care services. At the research level, the study could trigger the deepening on certain dimensions of the professional environment and the design could be replicated for the creation of similar studies in other countries and different cultures.
Keywords: Professional environment; Physicians; Nurses; Job satisfaction; Perceptions; Safety climate; Self-reported quality of care; Επαγγελματικό περιβάλλον; Ιατροί; Νοσηλευτές; Επαγγελματική ικανοποίηση; Απόψεις; Κλίμα ασφάλειας; Αυτοαναφερόμενη ποιότητα φροντίδας